"NUCLEAR CONSUMED LOVE": atomic threats and australian indigenous activist poetics. Issue 3 (3rd July 2017) - Hall, Matthew
Abstract: This essay will examine the polemic and poetic means through which three Indigenous Australian writers discuss the repercussions and risks associated with nuclear power, waste and weaponry as an existential and material threat to the mythopoeic creation stories, totemic systems and landforms which sustain Indigenous Australian belief. This essay will follow the establishment of a media ecology through which discourses of technological harm in Oodgeroo Noonuccal's "No More Boomerang" lay the foundation for Australian Indigenous anti-nuclear activist poetics and highlights the relationship between language, belief and technology. Oodgeroo's [Kath Walker] "No More Boomerang" will be read as a precursor to the experimental expression of Lionel Fogarty's "Foot Walking and Talking – Atomic Confusion" as well as the procedural methodologies behind Natalie Harkin's "Zero Tolerance." It will be argued that Indigenous-led representations of nuclear weaponry as an ontologic-existential threat can only be properly critiqued when framed through the constructs of race, nationhood and the history of colonization in Australia.